KARIKATUR TOKOH POLITIK INDONESIA DALAM KARYA LUKIS - Gusti Randa; Achyar Sikumbang; Minarsih . (Serupa The Journal of Art Education, 2012)
Abstract This final project is suppofed to visualize Indonesian politicians into caricature work. Politicians are people who has big impact to the social life comes from attitude, characters even its habit. Some of the politicians that will be covered in caricature work titled: 1). Gus Dur, 2). Habibie, 3). JUsuf Kalla, 4). Aburizal Bakrie, 5). Soekarno, 6). Soeharto, 7). SBY, 8). Surya Paloh, 9). Marzuki Alie, 10). Anas Urbaningrum. This tenth last project shows many problems in each of the Indonesian politicians.   Kata kunci : Karikatur, Tokoh, Politik, Lukis